Phasor measurement method based on soft synchronized sampling with temporal pulse signal reference - Zhang, Jie; Tang, Chao; Liu, Chun; Wang, Hai; Junfeng, Duan; Tang, Sihao (Frontiers in Energy Research, 2023)
Introduction: Phasor measurement is crucial for the monitoring and management of power grids. Traditional hardware-based phasor measurement units (PMUs) are effective but often complex and expensive. This paper introduces a software-based phasor measurement method that utilizes soft synchronization with temporal pulse signals from GPS and mobile communication stations, offering a simpler and cost-effective alternative. Methods: The proposed method synchronizes the local oscillator with Pulse Per Second (PPS) signals from GPS and primary synchronization signals from mobile communication bases. Raw data affected by the local oscillator’s instability are transformed into calibrated data using B-Spline interpolation to emulate an ideal sampling rate. The calibrated data are then subjected to a Recursive Discrete Fourier Transform (RDFT) algorithm for synchronized phasor measurement. Results: The method’s performance was assessed in compliance with the C37.118.1 standard. Key performance indicators, such as frequency, phase, and Total Vector Error (TVE), were evaluated. The proposed software-based approach demonstrated high accuracy in synchronized phasor measurements. Discussion: The results confirm that the proposed method can serve as a highly accurate and simpler alternative to conventional hardware-based solutions. Its application promises to advance synchronized phasor measurement practices in power grid monitoring, enhancing reliability and reducing complexity and costs.